Comparative Analysis of Axial Map Drawing Methods: Elazig Application - Sikoglu, Emrah (Konya Technical Univ, Fac Architecture & Design, 2021)
Purpose There are three basic methods used for creating axial maps in Space Syntax studies. Manual drawing is the first and most grounded method. The second method is the production of automatic axial maps with a tool, known as the Axial Map in the Depth Map program. The third and most modern method is the use of lines named Road Center Line (RCL). The primary goal of this study is to reveal the relationship between manual drawing, which is the first method used in creating axial maps and still regarded as the most reliable one, and other methods used in drawing axial maps. The other purposes of the study are analysing the features of methods used in creating axial maps, presenting the advantages and disadvantages of these methods, and comparing the methods. Accurately analysing wide spaces such as urban settlements and supporting Space Syntax studies for preventing drawing differences resulting from users in manual drawings are the other goals of this study. Design/Methodology/Approach The above mentioned three methods used for creating axial maps are compared in the study in terms of the period, morphological similarity, and analysis results. Analyses are carried out in Depth MapX and the Mapinfo program is used for arrangements. Findings The manual drawing method is the most time consuming one while the RCL maps technique is the least time-consuming. Automatic drawing creates the axial maps based on the very same rules, which makes it the closest technique to the traditional drawing method in terms of textural similarity. However, it is believed that both automatic drawing and RCL need improvement. Research Limitations/Implications Manuel Drawing takes a very long time. Therefore, only one application city (Elazig) could be selected in the study. Social/Practical Implications The practitioner who wants to decide which of these methods to choose can decide this by looking at this study. He/she can also have an idea of what to pay attention to when using the methods. Originality/Value In this study, three different axial map-drawing techniques were applied to a city. Besides, for the first time, three drawing techniques were compared and discussed in this study.
Keywords: Axial map; Elazig; road center line; space syntax; space syntax drawing methods